Small States in the Shadow of Great Power Politics - Bhattarai, Dinesh (NCWA Annual Journal, 2026)
This article examines how small states navigate an international system increasingly marked by a shifting geopolitical landscape and shaped by intensifying great power rivalry, strategic competition, and a move toward multipolarity. Moving beyond consideration of small states as passive actors or mere objects in international affairs, the study argues that they can exercise their influence through diplomatic agility, normative positioning, consensus-building, and strategic multilateralism as purposeful partners. Drawing on cases from regions such as the Indo-Pacific, Europe, and the Global South, the article demonstrates how small states employ strategies of hedging, healthy balancing, niche diplomacy, and international law to safeguard sovereignty and expand policy options and space amid pressures from larger powers. It attempts to discuss the condition of small states in a rapidly changing geopolitical landscape and the rise of the middle power. It examines how small states, drawing on their internal capacity and strong domestic foundations, balance relations with emerging middle powers and sustain engagements in the UN peacekeeping operations. Engaging with realism and liberal institutionalism, the article explains how vulnerability can be transformed into leverage. It highlights how small states use international organizations, economic interdependence, and normative commitments—such as peaceful coexistence, nonalignment and neutrality, and rule-based order—to resist coercion and maintain strategic autonomy. The article discusses the possible perspectives for a weak and vulnerable country like Nepal, perennially trapped in political transition and located between two huge neighbors, India and China, in a rapidly changing geopolitical landscape. It briefly touches on how Nepal conducts its foreign policy with its large neighbors and remains constructively engaged with great powers and the broader international community.  It argues that in an era of renewed great power competition, the survival and relevance of small powers depend less on material capabilities and more on their capacity to institutionalize external relationships, diversify partnerships, and build domestic capacity to influence international norms and standards to their advantage.